2007
DOI: 10.1128/iai.01727-06
|View full text |Cite
|
Sign up to set email alerts
|

Pneumolysin, PspA, and PspC Contribute to Pneumococcal Evasion of Early Innate Immune Responses during Bacteremia in Mice

Abstract: The pneumococcal virulence factors include capsule, PspA, PspC, and Ply. Cytometric analysis demonstrated that the greatest levels of C3 deposition were on a ⌬ply PspA ؊ PspC ؊ mutant. Also, Ply, PspA, and PspC expression resulted in C3 degradation in vitro and in vivo. Finally, blood clearance assays demonstrated that there was enhanced clearance of ⌬ply PspA ؊ PspC ؊ pneumococci compared to the clearance of nonencapsulated pneumococci.Streptococcus pneumoniae possesses virulence factors that function in evas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 29 publications
5
54
1
Order By: Relevance
“…As a cofactor of factor I, hFH can also cleave C3b to iC3b (11). In S. pneumoniae, loss of PspC (an hFH-binding surface protein) can cause reduced iC3b and increased C3b/iC3b (compatible with reduced C3 convertase activity) deposition on strains (37,45), which is similar to our data that loss of Fhb could increase C3b/iC3b and reduce iC3b deposition on the mutant. We hypothesized that Fhb could interact with hFH to inhibit activation of the alternative complement pathway by S. suis.…”
Section: Resultssupporting
confidence: 80%
“…As a cofactor of factor I, hFH can also cleave C3b to iC3b (11). In S. pneumoniae, loss of PspC (an hFH-binding surface protein) can cause reduced iC3b and increased C3b/iC3b (compatible with reduced C3 convertase activity) deposition on strains (37,45), which is similar to our data that loss of Fhb could increase C3b/iC3b and reduce iC3b deposition on the mutant. We hypothesized that Fhb could interact with hFH to inhibit activation of the alternative complement pathway by S. suis.…”
Section: Resultssupporting
confidence: 80%
“…Moreover, other proinflammatory factors, such as lipoteichoic acid and Ply, are likely to contribute. Indeed, it was shown that Ply, PspA, and CbpA (PspC) all contribute to pneumococcal evasion of early innate immune responses during bacteremia in mice (62,80). The involvement of proinflammatory cytokines, CXC chemokines, and cell adhesion molecules in pneumococcal meningitis is well established (31,60,74,82).…”
Section: Discussionmentioning
confidence: 99%
“…PLY's complement-activating property functions to reduce the accumulation of T cells, whereas its cytotoxicity increases neutrophil recruitment and contributes to T-cell suppression; neither has a major effect on the accumulation of B cells or macrophages (367). Simultaneously, PLY, aided by pneumococcal surface protein A (PspA), appears to be able to impair the complement system by inhibiting C3 deposition (368,369).…”
Section: Innate Immune Responses To Pftsmentioning
confidence: 99%